2012
DOI: 10.1177/1753465811434320
|View full text |Cite
|
Sign up to set email alerts
|

Rare alpha-1-antitrypsin variants: are they really so rare?

Abstract: Alpha-1-antitrypsin (α1-AT) deficiency is mainly evaluated in the diagnostic process of chronic obstructive pulmonary disease (COPD). Around 95% of individuals with severe α1-AT deficiency carry the PI*ZZ genotype. Little is known about the epidemiology of the remaining deficient α1-AT variants, which are called 'rare' due to their low prevalence. The retrospective revision of 3511 α1-AT deficiency determinations performed in Barcelona from 1998 to 2010 detected 1.6% of cases with rare α1-AT alleles, a rate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 23 publications
4
48
0
4
Order By: Relevance
“…More awareness campaigns are needed, especially among primary care physicians who care for most patients with COPD, particularly in early stages of the disease [23]. Another interesting difference is the higher prevalence of rare genotypes in Italy compared with Spain, which is in accordance with previous reports [24,25] and could be related to the differences between the two nationwide diagnostic algorithms [19]. A list of the rare genotypes reported in the two registries is available as online supplementary material.…”
Section: Discussionsupporting
confidence: 70%
“…More awareness campaigns are needed, especially among primary care physicians who care for most patients with COPD, particularly in early stages of the disease [23]. Another interesting difference is the higher prevalence of rare genotypes in Italy compared with Spain, which is in accordance with previous reports [24,25] and could be related to the differences between the two nationwide diagnostic algorithms [19]. A list of the rare genotypes reported in the two registries is available as online supplementary material.…”
Section: Discussionsupporting
confidence: 70%
“…Based on this information, the prevalence of having any two rare alleles would be less than one in 10 5 . However, there are substantial geographical differences in SERPINA1 polymorphisms [7] and no valid information of rare alleles in Denmark is available. Organic dust is a well-known contributor to the development of COPD.…”
Section: To the Editormentioning
confidence: 99%
“…Little is known about the epidemiology of the remaining deficient AAT variants, which are called 'rare' due to their low prevalence (2-4%). A recent Spanish study found that 1.6% of registered AATD patients had rare AAT alleles with Pi I and Pi Mmalton representing 54% of them [30]. Null variants are variable and a novel one was detected firstly in an Egyptian family in Southern Italy and known as Q0 Cairo.…”
Section: Rare Disease -Associated Deficiency and Null Allelesmentioning
confidence: 99%